Dual-energy X-ray absorptiometry body composition in patients with secondary osteoporosis. Issue 8 (August 2016) - Messina, Carmelo; Monaco, Cristian Giuseppe; Ulivieri, Fabio Massimo; Sardanelli, Francesco; Sconfienza, Luca Maria
Highlights: DXA is an accurate and reproducible technique to assess body composition. DXA offers diagnostic and research possibilities in secondary osteoporosis patients. The main clinical applications of DXA body composition are provided. Abstract: Due to the tight relationship between bone and soft tissues, there has been an increased interest in body composition assessment in patients with secondary osteoporosis as well as other pathological conditions. Dual-energy X-ray absorptiometry (DXA) is primarily devoted to the evaluation of bone mineral status, but continuous scientific advances of body composition software made DXA a rapid and easily available technique to assess body composition in terms of fat mass and lean mass. As a result, the International Society for Clinical Densitometry (ISCD) recently developed Official Positions regarding the use of this technique for body composition analysis. According to ISCD paper, indications are mainly limited to three conditions: HIV patients treated with antiretroviral agents associated with a risk of lipoatrophy; obese patients undergoing treatment for high weight loss; patients with sarcopenia or muscle weakness. Nevertheless, there are several other interesting clinical applications that were not included in the ISCD position paper, such as body composition assessment in patients undergoing organ transplantation, pulmonary disease as well as all those chronic condition that may lead to malnutrition. In conclusion, DXA body composition offers new diagnostic and research possibilities for a variety of diseases; due to its high reproducibility, DXA has also the potential to monitor body composition changes with pharmacological, nutritional or physic therapeutic interventions. ISCD addressed and recommended a list of clinical condition, but the crescent availability of DXA scans and software improvements may open the use of DXA to other indication in the next future. This article provides an overview of DXA body composition indications in the management of secondary osteoporosis and other clinical indications in adults.